The Role of Parenting in Developing Self-Resilience and Self-Regulated Learning: An Islamic Educational Psychology Perspective - Rouzi‬, ‪Kana Safrina; Bin Husen Ismail, Faisal; Afifah, Ni'mah; Rochaendi, Endi; Musyrifah, Farida; Khauro’, Ma’nusatul (International Journal of Islamic Educational Psychology, 2025)
The frequent changes in learning modalities, especially during the post-pandemic period, have required students to adapt continuously. This study explores the role of parenting in cultivating students’ self-resilience and self-regulated learning (SRL) through the lens of Islamic educational psychology. Applying Fazlur Rahman's Double Movement Hermeneutic, the study offers a contextual interpretation of Qur’anic principles that emphasize ethical, reflective, and autonomy-supportive parenting. Through a systematic literature review, the study synthesizes interpretations of the Qur’an, Islamic parenting models, and psychological theories—particularly those of Baumrind—on resilience and SRL. Qualitative content analysis reveals key themes connecting Islamic parenting values—moral responsibility, sincere intention, and spiritual trust—with enhanced student resilience and self-regulation. The findings indicate that parenting practices rooted in Islamic teachings—moral responsibility, intention, and spiritual reliance—significantly foster resilience and SRL. This integrative approach contributes a faith-informed framework to psychological development and educational transformation in Muslim contexts.